Model Fisik Canal Blocking Bentuk Tabung - Ricca, Randi Rangkuti Putra; Rinaldi, Rinaldi; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Canal blocking is closure or insulation of trenches, rivers, or canals permanent or non-permanent that serve to keep the water system and elevation water level stable. With the canal blocking it will affect the flow profile in the channel. The purpose of this research is to investigate the effect of debit coefficient on canal blocking and the influence of bolt and shear force on the stability of canal blocking so as to produce optimal design. The study was conducted in the laboratory by testing the physical model of the blocking canal door. Canal blocking model is made in such a way resembles canal blocking in the field with a scale of 1: 7. Test method is done by variation of the discharge, permeable or unpermeable flow properties, tube arrangement, material weight, and canal blocking of one unit or not a single unit. The results showed that blocking canals have good stability, high efficiency, and economical influenced by several factors, there are type of material, the arrangement and the weight of the material content, the strength of the coefficient of friction (locking / recognition of canal blocking), and the design of permeable or unpermeable.Keywords: canal blocking model, permeable, unpermeable